Eksistensi Manusia Dalam Pancasila Perspektif Jean-Paul Sartre - Sultan Maulana, Dimas Rangga (Pancasila and Civics Education Journal, 2024)
This article discusses human existence in Pancasila. The discussion will focus mainly on the second principle which reads "Just and civilized humanity". In the second principle of Pancasila, the author sees how human existence exists there. Humans can be said to have existence if they act fairly and morally towards others. Based on this, the author tries to see how human existence in Pancasila cannot be separated from the divine aspect, seen from the perspective of Sartre's existentialism which tends to be more atheistic. In compiling this article, the method used was descriptive-analysis. The author explains material obtained from several sources such as books and articles, then the data obtained is processed to achieve an understanding of Pancasila and Sartre's existentialism. In this article, the author tries to explain the second principle of Pancasila and how human existence in it is then seen from the perspective of Sartre's existentialism. Pancasila, which has a theistic character, is seen from the perspective of Sartre's existentialism, which is seen as more atheistic in nature.